A Phenomenon of Modern Slavic Microphilology in Slavic Studies - Дмитриевич Дуличенко, Александр (Poznańskie Studia Slawistyczne, 2015)
The article addresses a phenomenon of Slavic microphilology, outlines the structure and classification of modern Slavic literary microlanguages, introduces their different characteristic, and suggests arguments in favour of forming of Slavic microlinguistics and microphilology.